2009
DOI: 10.1007/s00417-009-1150-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of vision screening tests for the detection of amblyopia and its risk factors: a systematic review

Abstract: Diagnostic test accuracy of preschool vision screening tests can only be sufficiently investigated after establishing age-related values defining amblyopia, refractive errors and binocular disorders. To address these questions, we recommend a controlled longitudinal study design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 43 publications
0
25
0
3
Order By: Relevance
“…Other commercial devices that have used this measurement principle include: iScreen Vision, MTI PS-100 Photoscreener, PlusOptix S08 AutoRefractor/Photoscreener (Previous models were PowerRefractor and Plusoptix S04, current version is S09), Right Medical Retinomax Autorefractor, Visiscreen OSS-C, Welch Allyn SureSight Autorefractor, Fortune Optical VRB-100 videophotorefractor. [5][6][7][8] Various studies suggest that non-cycloplegic photorefraction has reasonable accuracy and repeatability compared with cycloplegic retinoscopy and subjective refraction. However, in a study it was demonstrated that accommodation may not be completely neutralized.…”
Section: Introductionmentioning
confidence: 99%
“…Other commercial devices that have used this measurement principle include: iScreen Vision, MTI PS-100 Photoscreener, PlusOptix S08 AutoRefractor/Photoscreener (Previous models were PowerRefractor and Plusoptix S04, current version is S09), Right Medical Retinomax Autorefractor, Visiscreen OSS-C, Welch Allyn SureSight Autorefractor, Fortune Optical VRB-100 videophotorefractor. [5][6][7][8] Various studies suggest that non-cycloplegic photorefraction has reasonable accuracy and repeatability compared with cycloplegic retinoscopy and subjective refraction. However, in a study it was demonstrated that accommodation may not be completely neutralized.…”
Section: Introductionmentioning
confidence: 99%
“…The New Zealand Vision Hearing Screening program, which has existed for over 40 years, attempts to screen all children at ages four to five and 11 years for vision and hearing problems; however, there is a lack of consistent evidence on the robustness of vision screening programs, 1 the best screening tests to use, the most appropriate referral criteria and which screening personnel to utilise 1,2 . Much of the current research on children's vision screening programs focuses on the efficacy of various screening tools for identifying preschool children with amblyopia, 3,4 strabismus 5 and significant refractive errors 6 .…”
mentioning
confidence: 99%
“…There has been much debate about the efficacy of primary visual screening in many countries across Europe, [2][3][4][5] the USA and Canada, [6][7][8] Australia, 8,9 Asia 10-14 and the Middle East. [15][16][17][18] Many aspects of visual screening in the UK have been examined including: age at testing, 19,20 tests used, [21][22][23] personnel undertaking the screening, [24][25][26] referral criteria, 21,27 and cost-effectiveness. 28 For a primary visual screening programme to be viable it has to have excellent coverage of the target group 29,30 and show the highest possible levels of sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Many aspects of visual screening in the UK have been examined including: age at testing, 19,20 tests used, [21][22][23] personnel undertaking the screening, [24][25][26] referral criteria, 21,27 and cost-effectiveness. 28 For a primary visual screening programme to be viable it has to have excellent coverage of the target group 29,30 and show the highest possible levels of sensitivity and specificity. 28,30,31 The results of this audit of screening visual acuities falling between 0.15 logMAR and 0.20 logMAR inclusive showed a false referral rate of 18.9% if the false referral is taken as the child not needing any follow-up.…”
Section: Discussionmentioning
confidence: 99%